Plant Ecology An International Journal - Enright, Neal.; Rogers, William Edward; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
Plant Ecology publishes original scientific papers that report and interpret the findings of pure and applied research into the ecology of vascular plants in terrestrial and wetland ecosystems. Empirical, experimental, theoretical and review papers reporting on ecophysiology, population, community, ecosystem, landscape, molecular and historical ecology are within the scope of the journal.
Keywords: Ecology; Applied ecology; Biodiversity; Plant ecology; Community ecology, Biotic; Ecology; Plant Ecology; Community & Population Ecology; Terrestial Ecology; Applied Ecology; Biodiversity